Non-Invasive Positive airway Pressure thErapy to Reduce Postoperative Lung complications following Upper abdominal Surgery (NIPPER PLUS): a pilot randomised control trial. (December 2022) - Lockstone, J.; Parry, S.M.; Denehy, L.; Robertson, I.K.; Story, D.; Boden, I.
Abstract: Objectives: Postoperative pulmonary complications (PPCs) are a common serious complication following upper abdominal surgery. Postoperatively, physiotherapy-led non-invasive ventilation (NIV) may be a promising method to reduce PPC incidence. The objectives of this pilot trial were to examine preliminary effectiveness, feasibility and safety of additional intermittent physiotherapy-led NIV compared to continuous high-flow nasal cannula oxygen therapy (HFNC) alone. Design: Single-centre, assessor-blinded, parallel-group, pilot randomised control trial. Setting: Primary-referral hospital in Australia. Participants: 130 high-risk patients undergoing upper abdominal surgery. Interventions: Continuous HFNC for 48-hours following surgical extubation, or HFNC plus five 30-minute physiotherapy-led NIV sessions. Outcomes: PPC incidence, trial feasibility and safety. Results: PPC incidence was similar between groups (HFNC alone 12/65 (18%) vs HFNC plus NIV 10/64 (16%) adjusted HR 0.95; 95% CI 0.40–2.29). Delivery of HFNC as per-protocol was achieved in 81% (n = 105) of all participants. Physiotherapy-led NIV initiated within four-hours of surgical extubation was achieved in 81% ( n = 52) of intervention group participants, with a mean 4.2 (SD 1.3) total number of NIV sessions delivered in the first two postoperative days. NIV was delivered as per-protocol in 52% of this cohort. Two episodes of severe hypotension during NIV requiring medical intervention were reported. Conclusion: Delivery of continuous HFNC was feasible. Delivery of NIV within four-hours of extubation was achieved and delivered safely with< 1% adverse events. The planned NIV intervention of five sessions within two postoperative days was not feasible. The results of this pilot study have informed the decision not to proceed to a fully powered trial. Clinical Trial Registration: Australian New Zealand Clinical Trials Registry, www.anzctr.org.au ACTRN12617000269336. Contribution of the Paper: A protocol of continuous postoperative HFNC is feasible, well-tolerated and acceptable to high-risk adults following elective upper abdominal surgery. Prophylactic physiotherapy-led NIV within the early postoperative period is feasible in some cases. Physiotherapy-led NIV can be delivered safely to high-risk adults following elective upper abdominal surgery in the post-anaesthetic care unit, ICU and surgical ward setting. Delivery of a physiotherapy-led NIV protocol of five sessions over two postoperative days is not feasible to warrant progression to a future definitive trial.